2022
DOI: 10.3389/fmicb.2022.1032873
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the effects of sulfamethoxazole on the composition of gut microbiota and immune responses in Stichopus variegatus

Abstract: The aim of this work was to reveal the changes in gut microbiota composition and immune responses of sea cucumber (Stichopus variegatus) after being affected by different doses of sulfamethoxazole. In this study, the bacterial 16S rRNA of gut microbiota were analyzed by high-throughput sequencing, and the activities of immune enzymes [lysozyme (LZM), phenoloxidase (PO), alkaline phosphatase (AKP), and acid phosphatase (ACP)] in the gut of S. variegatus were determined. The results showed that the gut microbiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Additionally, SSO attacks lead to fish flavor deterioration, notably freshness loss and bad odor development [3]. A large number of studies have shown that the shelf-life of large yellow croaker can be effectively extended by vacuum preservation [4]. However, some spoilage microorganisms can still grow even in vacuum packaging, which can damage the quality of the fish.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, SSO attacks lead to fish flavor deterioration, notably freshness loss and bad odor development [3]. A large number of studies have shown that the shelf-life of large yellow croaker can be effectively extended by vacuum preservation [4]. However, some spoilage microorganisms can still grow even in vacuum packaging, which can damage the quality of the fish.…”
Section: Introductionmentioning
confidence: 99%